Monitoring and Reporting of Adverse Drug Reactions Due to Cardiovascular Drugs in Patients Admitted to a Secondary Care Hospital in Northern Emirate- A Prospective Surveillance Study - Wadhwa, Tarun; Sheikh, Samar Gamal El; Rao, Padma G.M. (Indian Journal of Pharmacy Practice)
Context: Adverse drug reactions (ADRs) can result in a number of consequences, ranging from allergic reactions to permanent harm thereby causing morbidity and mortality leading to an increase in the health care costs. Aims: The main objective of the present study was to assess the prevalence of adverse drug reactions due to cardiovascular drugs in patients admitted to a secondary care hospital. Material and Methods: This was a prospective surveillance study which included adult patients of either gender who were hospitalized and prescribed with at least one cardiovascular drug. Patients were monitored from the day of admission till the day of discharge for the occurrence of ADRs due to cardiovascular drugs by attending clinical meetings, ward rounds, reviewing patients’ medical records and electronic medical records. Results: A total of 309 patients were enrolled in the present study. Among them, 72 patients experienced 109 ADRs accounting for an incidence of 23.3%. Twelve (3.88%) patients were hospitalized due to ADRs (n=16) whereas 60 (19.41%) patients developed ADRs (n=93) during their hospital stay. Male preponderance was observed over female. Patients with age ≥ 60 years experienced 73 ADRs. The most common drug class implicated in ADRs was observed to be beta blockers (18; 16.5%) especially bisoprolol (16; 14.68%). Majority of patients experienced bradycardia (11; 10.09%) followed by hypotension (9; 8.26%). Cardiovascular system (30; 27.53%) was observed to be the most common system. Majority of ADRs were possible (80; 73.39%) in nature, mild (53%) in severity and not preventable (84.5%). Conclusion: Intensive approach towards monitoring and reporting of ADRs could help healthcare professionals in minimizing preventable ADRs. Key messages: Study demonstrated high incidence of adverse drug reactions in patients on cardiovascular drugs. This triggers an alarming signal for vigilant monitoring of patients to prevent further recurrence
Keywords: Adverse drug reaction; Cardiovascular drugs; Causality; Pharmacovigilance; Preventability; Severity.